Impact of Changes in the Optical Density of Postlens Fluid on the Clinical Performance of Miniscleral Lenses - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Purpose: To determine the impact of optical density changes in postlens fluid on clinical performance and to quantify these changes over time during miniscleral lens wear. Methods: Twenty-three eyes of 13 patients with keratoconus were fitted with a miniscleral lens (scleral Misa lenses; Microlens Contactlens Technology, Arnhem, Netherlands). The lens fit was evaluated using the fluorescein pattern and also through anterior segment optical coherence tomography imaging. The optical density changes were measured using Scheimpflug tomography at 30 min, 1, 2, 3, and 4 hr. High- and low-contrast visual acuity (VA), subjective performance with comfort and vision (5-point Likert scale), and overall satisfaction with the lens (100-mm visual analog scale) were measured before and after lens-wear. Results: The mean Snellen high-contrast VA (best spectacle-corrected VA: 0.4 +/- 0.2 vs. VA with the scleral lens: 0.8 +/- 0.1, P0.0001) and low-contrast VA (best spectacle-corrected VA: 1.2 +/- 0.2 vs. VA with the scleral lens: 1.3 +/- 0.2, P=0.019) significantly improved with dispensed scleral lens. Patients reported high scores for comfort (3.8 +/- 0.8), vision (3.8 +/- 0.6), and overall satisfaction with the lens (68.7 +/- 19.1). Compared with preoperative values, optical density significantly increased over time (P0.0001). High-contrast VA remained stable, whereas low-contrast VA significantly decreased at 2 hr (P=0.035). Conclusion: This study shows that the optical density of postlens fluid increases over time with miniscleral lens wear, and it has a negative impact on low-contrast VA.
Keywords: Keratoconus; Optical density; Postlens fluid; Scleral lenses; SCLERAL CONTACT-LENS; KERATOCONUS; CHALLENGES